2022
DOI: 10.1093/nar/gkac884
|View full text |Cite
|
Sign up to set email alerts
|

isomiRdb: microRNA expression at isoform resolution

Abstract: A significant fraction of mature miRNA transcripts carries sequence and/or length variations, termed isomiRs. IsomiRs are differentially abundant in cell types, tissues, body fluids or patients’ samples. Not surprisingly, multiple studies describe a physiological and pathophysiological role. Despite their importance, systematically collected and annotated isomiR information available in databases remains limited. We thus developed isomiRdb, a comprehensive resource that compiles miRNA expression data at isomiR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…These variants, known as isomiRs, are reported to have different turnover rates [4,34]. Interestingly, using the isomiRdb database [15], we found that two noncanonical isomiRs of miR‐133a (5′‐end trimmed and 3′‐end U‐tailed, and 3′‐end U‐tailed) are more abundant than its canonical isoform in muscle (Fig. 5A), whereas the most abundant isomiR of miR‐1 is the canonical isoform (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These variants, known as isomiRs, are reported to have different turnover rates [4,34]. Interestingly, using the isomiRdb database [15], we found that two noncanonical isomiRs of miR‐133a (5′‐end trimmed and 3′‐end U‐tailed, and 3′‐end U‐tailed) are more abundant than its canonical isoform in muscle (Fig. 5A), whereas the most abundant isomiR of miR‐1 is the canonical isoform (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Because miR-1 had a short half-life in our dataset, we assumed it to have a quite high turnover rate. MiR-206 is a skeletal-muscle-specific miRNA belonging to the same miRNA family as miR-1 [27] that shares sequences identical to those of miR-1, including the seed sequences and an additional supplementary pairing region (nucleotides [13][14][15][16]. Several miRNA families that share seed sequences have been shown to have similar decay rates in mouse fibroblasts [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms behind isomiR formation have, in general, been revealed: beside the subtle regulation of the main miRNA processing enzymes (Drosha and Dicer), the action of terminal nucleotidyl transferases, exoribonucleases and RNA editing enzymes are also responsible for the existence of certain isomiR groups (Tomasello et al 2021). On the other hand, the regulation of cell-type specific isomiR distribution is still not completely understood and this aspect is currently in the focus of intensive investigations (Zelli et al 2021;Aparicio-Puerta et al 2023). Nevertheless, isomiRs should definitely be considered in miRNA target predictions (Ahmed et al 2014), as well as in the development of new diagnostic tools and in planned therapy applications (Nikolova et al 2021;Scheper et al 2022).…”
Section: Formation Of Isomirs-substantially Increasing the Mirna Repe...mentioning
confidence: 99%